2015
DOI: 10.1515/folmed-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigations. Comparison of Directigen Flu A+B with Real Time PCR in the Diagnosis of Influenza / Сравнение Иммунохроматографического Метода (Directigen Flu A+B) И Теста RT-PCR При Инфекциях Гриппа

Abstract: Directigen Flu A+B has relatively low sensitivity for detection of influenza viruses in combined nose and throat swabs. Negative results must be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Our aim was to evaluate the performance of six FDA-cleared STA FluA/B and RSV molecular assays compared to the results of the Centers for Disease Control and Prevention (CDC) influenza virus real-time RT-PCR (rRT-PCR) and RSV rRT-PCR assays as the reference methods (14,23,24). Multiple studies have reported the enhanced performance of the CDC Flu A/B rRT-PCR assay over other diagnostic assays (25)(26)(27). Moreover, typing of FluA/B into the respective subtypes by the CDC rRT-PCR method provides conclusive evidence for discrepant analysis.…”
mentioning
confidence: 99%
“…Our aim was to evaluate the performance of six FDA-cleared STA FluA/B and RSV molecular assays compared to the results of the Centers for Disease Control and Prevention (CDC) influenza virus real-time RT-PCR (rRT-PCR) and RSV rRT-PCR assays as the reference methods (14,23,24). Multiple studies have reported the enhanced performance of the CDC Flu A/B rRT-PCR assay over other diagnostic assays (25)(26)(27). Moreover, typing of FluA/B into the respective subtypes by the CDC rRT-PCR method provides conclusive evidence for discrepant analysis.…”
mentioning
confidence: 99%